High-throughput Procedure for the Peat Soil Reference Sample Stabilization Using Microwave Radiation - Keiti Oliveira Alessio; Maria Viviane Gomes Muller; Aline Teichmann; Eduardo Alexis Lobo; Adilson Ben da Costa (Orbital: The Electronic Journal of Chemistry, 2017)
Reference materials used in quality control laboratories need to maintain homogeneity and stability that can be affected by temperature, humidity and microbial activity. This research aimed to investigate a rapid, cheap and high-throughput procedure, using microwave radiation for the inhibition of microbial growth in peat reference sample, in order to increase its stability. Different exposure times (60, 120 and 180 seconds) of the material to radiation were evaluated, and the microbiological tests were conducted to assess the percentage reduction in CFUs for fungi and bacteria. The results showed 100% and >90% of reduction in growth for bacterial and fungi, respectively, over 90 days of monitoring the material, using 120 to 180 seconds of microwave radiation exposure times. The results demonstrate that this method is economical and efficient at stabilizing peat reference materials.DOI: http://dx.doi.org/10.17807/orbital.v9i5.942